Acute encephalopathy with elevated CSF inflammatory markers as the initial presentation of COVID-19 - Farhadian, Shelli; Glick, Laura R.; Vogels, Chantal B. F.; Thomas, Jared; Chiarella, Jennifer; Casanovas-Massana, Arnau; Zhou, Jing; Odio, Camila; Vijayakumar, Pavithra; Geng, Bertie; Fournier, John; Bermejo, Santos; et al. (BMC neurology, 2020)
Background COVID-19 is caused by the severe acute respiratory syndrome virus SARS-CoV-2. It is widely recognized as a respiratory pathogen, but neurologic complications can be the presenting manifestation in a subset of infected patients. Case presentation We describe a 78-year old immunocompromised woman who presented with altered mental status after witnessed seizure-like activity at home. She was found to have SARS-CoV-2 infection and associated neuroinflammation. In this case, we undertake the first detailed analysis of cerebrospinal fluid (CSF) cytokines during COVID-19 infection and find a unique pattern of inflammation in CSF, but no evidence of viral neuroinvasion. Conclusion Our findings suggest that neurologic symptoms such as encephalopathy and seizures may be the initial presentation of COVID-19. Central nervous system inflammation may associate with neurologic manifestations of disease.